Reading Loss - Demir, Danyela (Logos Verlag Berlin, 2019)
This book focuses on six post-apartheid novels, namely Zo¨e Wicomb's ''Playing in the Light'' (2006), Marlene van Niekerk's ''Agaat'' (2004/2007), André Brink's ''Devil's Valley'' (1998), Sarah Penny's ''The Beneficiaries'' (2002), K Sello Duiker's ''Thirteen Cents'' (2000), and Kgebetli Moele's ''Room 207'' (2006). It aims at highlighting different manifestations of melancholia that are visible in these texts in particular and in post-apartheid writing more generally. Mainly based on Sigmund Freud's, Anne Cheng's, and Paul Gilroy's concepts of melancholia, most novels are regarded as melancholic counter-narratives to the South African Truth and Reconciliation Commission's attempt to initiate a nationwide process of mourning with the aim of subsequent closure of the apartheid past. Moreover, concepts of melancholia prove particularly useful in order to analyse issues such as complicity, uncritical whiteness, crises of identity, forms of resistance, and intergenerational memory.